Measurement of craving among gamers with internet gaming disorder using repeated presentations of game videos: a resting-state electroencephalography study - Park, Sangin; Ha, Jihyeon; Ahn, Wonbin; Kim, Lae hyun (BioMed Central, 2023)
Background Internet gaming disorder (IGD) is receiving increasing attention owing to its effects on daily living and psychological function. Methods In this study, electroencephalography was used to compare neural activity triggered by repeated presentation of a stimulus in healthy controls (HCs) and those with IGD. A total of 42 adult men were categorized into two groups (IGD, n？=？21) based on Y-IAT-K scores. Participants were required to watch repeated presentations of video games while wearing a head-mounted display, and the delta (D), theta (T), alpha (A), beta (B), and gamma (G) activities in the prefrontal (PF), central (C), and parieto-occipital (PO) regions were analyzed. Results The IGD group exhibited higher absolute powers of DC, DPO, TC, TPO, BC, and BPO than HCs. Among the IGD classification models, a neural network achieves the highest average accuracy of 93% (5-fold cross validation) and 84% (test). Conclusions These findings may significantly contribute to a more comprehensive understanding of the neurological features associated with IGD and provide potential neurological markers that can be used to distinguish between individuals with IGD and HCs.